2006
DOI: 10.1007/s11103-006-9038-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression, and cytokinin (6-benzylaminopurine) antagonist activity of peanut (Arachis hypogaea) lectin SL-I

Abstract: Isolation and purification of a alpha-methyl-mannoside specific lectin (SL-I) of peanut was reported earlier [Singh and Das (1994) Glycoconj J 11:282-285]. Native SL-I is a glycoprotein having approximately 31 kDa subunit molecular mass and forms dimer. The gene encoding this lectin is identified from a 6-day old peanut root cDNA library by anti-SL-I antibody and N-terminal amino acid sequence homology to the native lectin. Nucleotide sequence derived amino acid sequence of the re-SL-I shows amino acid sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Goldthwaite and Laetsch (1967) analyzed the regulation of senescence of bean leaf discs in response to 6-BAP and found that 6-BAP reduced the loss of chlorophyll and protein from the leaf discs. Similarly, cytokinins (kinetin and 6-BAP) were effective in retarding senescence in leaf discs of Rumex (Goldthwaite and Laetsch, 1968) and N. tabacum (Pathak et al, 2006). Thus the present findings suggest that the association of cpcb with leaf senescence in Picrorhiza might also be regulated through cytokinin.…”
Section: Time (Hours)supporting
confidence: 66%
“…Goldthwaite and Laetsch (1967) analyzed the regulation of senescence of bean leaf discs in response to 6-BAP and found that 6-BAP reduced the loss of chlorophyll and protein from the leaf discs. Similarly, cytokinins (kinetin and 6-BAP) were effective in retarding senescence in leaf discs of Rumex (Goldthwaite and Laetsch, 1968) and N. tabacum (Pathak et al, 2006). Thus the present findings suggest that the association of cpcb with leaf senescence in Picrorhiza might also be regulated through cytokinin.…”
Section: Time (Hours)supporting
confidence: 66%
“…Recently, additionally to their saccharide specificity, it has been found that many plant lectins have hydrophobic sites for hydrophobic non-carbohydrate compounds (4,10,16,21,24,26,29). It is supposed that they are biologically relevant which is shown by their higher affinity for hydrophobic ligands than to carbohydrate ones.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, in addition to their carbohydrate-binding capacity, it has been discovered that some plant lectins have hydrophobic sites for adenine and physiological compounds. [2][3][4][5][6][7][8] The affinity towards these physiological non-carbohydrate ligands was higher than their affinity for carbohydrates indicating that the interaction with hydrophobic ligands may be biologically relevant. Similarly, some animal lectins have non-carbohydrate-binding domains, [9][10][11] and it is shown that they bind non-carbohydrate ligands through hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%